The influence of steaming pretreatment on sugars recovery upon completing hydrolysis process from residual starch of sago hampas - Siti Shawati, binti Wasli (Universiti Malaysia Sarawak (UNIMAS), 2015)
Currently, there is a wide utilisation of agricultural waste especially sago hampas where the hampas which contains starch and lignocellulose, has shown its capability to be converted into sugar through enzymatic and acid hydrolysis. These sugars can be further fermented and converted into value added products such as bioethanol. However, residual starch in sago hampas are trapped in the lignocellulose matrix and natural lignocellulose does not undergo enzymatic hydrolysis efficiently due to the nature of the lignocellulosic structure. Steaming pretreatment of lignocellulosic compound alters the construction of cellulosic biomass which causes the starch and cellulose in the plant fibres to be exposed and be more accessible. The focus of this study is the recovery of sugar from residual starch of sago ham pas through steaming pretreament and enzymatic hydrolysis of starch. 7% substrate load of sago hampas at pH 4 shows the highest hydrolysis yield of69.04% at only 30 min while 10% substrate load shows the highest yield at pH 5 and 30 min with hydrolysis yield of 65.49%. Significant difference in glucose concentration can be observed when compared to the controls ofthe experiment thus steaming pretreatment influences the sugars recovery of residual starch ofsago harnpas.